Epigallocatechin-3-gallate suppresses proinflammatory cytokines and chemokines induced by Toll-like receptor 9 agonists in prostate cancer cells - Mukherjee S (Dove Medical Press, 2014)
Sushovita Mukherjee, Mohammad Adnan Siddiqui, Shubham Dayal, Yasmine Zakaria Ayoub, Krishnamurthy Malathi Department of Biological Sciences, University of Toledo, Toledo, OH, USA Abstract: Chronic inflammation of the prostate contributes to the increased risk of prostate cancer. Microbial pathogens in the prostate cause inflammation that leads to prostatitis and proliferative inflammatory atrophy frequently associated with the development of prostate cancer. Bacterial lipopolysaccharides and DNA mediate immune responses by engaging Toll-like receptor (TLR) 4 and 9, respectively. Synthetic oligodeoxynucleotides containing CpG motifs (CpG-ODN) mimic bacterial DNA and signal through TLR9 to initiate innate immune responses. Here, we show that stimulation of DU145, PC3, or LnCap prostate cancer cells by the TLR9 agonists, CpG-ODN, induces mRNA expression of IL-6, IL-8, CXCL1, IP-10, CCL5, and TGFβ. In addition, activity of matrix metalloproteinase (MMP)-9 and -2 and cell migration increased on CpG-ODN treatment. Induction of cytokines and chemokines was mediated by NF-ΚB activation and translocation to the nucleus. Treatment with epigallocatechin-3-gallate (EGCG), the major constituent of green tea, prior to CpG-ODN stimulation, inhibits cytokine and chemokine gene induction, activity of MMP-9 and -2, and cell migration. EGCG treatment sequesters the p65 subunit of transcription factor NF-ΚB in the cytoplasm and inhibits transcriptional activity of the NF-ΚB-driven promoter in response to CpG-ODN. Our results suggest that the ability of the TLR9 agonists, CpG-ODN, to induce cytokines, chemokines, and MMP activity, as well as suppression by EGCG are independent of the androgen receptor and p53 status of the cells. EGCG may provide protective effects against inflammation in the prostate and benefit prostate cancer treatment. Keywords: CpG-ODN, EGCG, inflammation, NF-ΚB